IEEE Conference on Decision and Control and European Control Conference 2011
DOI: 10.1109/cdc.2011.6160337
|View full text |Cite
|
Sign up to set email alerts
|

Topological equivalence of a structure-preserving power network model and a non-uniform Kuramoto model of coupled oscillators

Abstract: Abstract-We study synchronization in the classic structurepreserving power network model proposed by Bergen and Hill. We find that, locally near the synchronization manifold, the phase and frequency dynamics of the power network model are topologically conjugate to the phase dynamics of a non-uniform Kuramoto model and decoupled exponentially stable dynamics for the frequencies. This topological conjugacy implies the equivalence of local exponential synchronization in power networks and in non-uniform Kuramoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…It has been revealed that parameterized systems of the form have the identical equilibrium set and the identical local stability properties for all λ ∈ [0,1] as stated in the following theorem: Theorem For the one‐parameter family scriptHλ of dynamical systems in , the following statements hold independently of the parameter λ ∈ [0,1]. Equilibrium set: For all λ ∈ [0,1], the equilibrium set of scriptHλ is given by the set of critical points of the potential function ψ , that is, E p , v = {[ p T v T ] T : ∇ ψ = 0}. Local stability: For any equilibrium [ p T v T ] T ∈ E p , v and for all λ ∈ [0,1], the numbers of the stable, neutral, and unstable eigenvalues of the Jacobian of scriptHλ are not dependent on λ .…”
Section: Undirected Formations Of Double Integratorsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been revealed that parameterized systems of the form have the identical equilibrium set and the identical local stability properties for all λ ∈ [0,1] as stated in the following theorem: Theorem For the one‐parameter family scriptHλ of dynamical systems in , the following statements hold independently of the parameter λ ∈ [0,1]. Equilibrium set: For all λ ∈ [0,1], the equilibrium set of scriptHλ is given by the set of critical points of the potential function ψ , that is, E p , v = {[ p T v T ] T : ∇ ψ = 0}. Local stability: For any equilibrium [ p T v T ] T ∈ E p , v and for all λ ∈ [0,1], the numbers of the stable, neutral, and unstable eigenvalues of the Jacobian of scriptHλ are not dependent on λ .…”
Section: Undirected Formations Of Double Integratorsmentioning
confidence: 99%
“…Formation dynamics of the agents under the control law can be described as a dissipative Hamiltonian system. On the basis of the topological equivalence of the dissipative Hamiltonian system and a gradient system, which has been studied in [9], we show that the local asymptotic stability of the undirected formations of double-integrator modeled agents is achieved. Although the author of [10] has addressed the stability of undirected formations of double-integrator modeled agents by means of the LaSalle invariance principle, as pointed out in [1], it is not certain whether the principle can be applied because the equilibrium set of the formation dynamics is not compact.…”
Section: Introductionmentioning
confidence: 99%
“…IDENTIFICATION To identify generator coherency, we make use of insights recently presented by Dörfler and Bullo in [4] whereby it is shown via singular perturbation analysis that Eq. (1) is equivalent to:…”
Section: Spectral Matrix-based Generator Coherencymentioning
confidence: 99%
“…Consequently the degrading of coupling strength with distance is lowered. The peak magnitude appears to be bounded despite further increase in R. Remark 7: Non-uniform Kuramoto dynamics (10) are related to those of network models for power systems via a toplogical equivlance only of the equilibria, not the full dynamics [14]. In that light the phenomenon of peaking becomes more interesting, because it develops on grounds of an "almost" (i.e.…”
Section: Numerical Studymentioning
confidence: 99%
“…Condition (26b) suggests quasi-stationarity as varying χ Ω (t) where in intervals n 2π ω ≤ t < (n + 1) 2π ω , n ∈ N attraction and repulsion balance up to a constant to yield arbitrary small oscillations as follows: Frequency entrainment corresponds to exponential synchronization to some bounded frequencyΘ s ∈ [Θ min ,Θ max ], and phase locking to positive invariance of the set of bounded phase differences Θ ∈ T N : max ik∈E |Θ ik | ≤ γ , see [5]. Assume exponentially small differences of the form Θ i − Θ i−k = Θ i − Θ i+k , and substituting into the lumped parameter dynamics (22) gives together with (14) for the sinusoidal phase interaction while the cosine interaction term expanded similarly results in…”
Section: B Dynamics and Stationary Solutionsmentioning
confidence: 99%